Comparison of Fe(VI) (FeO4(2-)) and Ozone in Inactivating Bacillus Subtilis Spores - Makky, Essam A.; Park, Gui-Su; Choi, Ik-Won; Cho, Sung-Il; Kim, Hyunook (Elsevier, 2011)
The protozoan parasites such as Cryptosporidiumparvum and Giardialamblia have been recognized as a frequent cause of recent waterborne disease outbreaks because of their strong resistance against chlorine disinfection. In this study, ozone and Fe(VI) (i.e., FeO(4)(2-)) were compared in terms of inactivation efficiency for Bacillus subtilis spores which are commonly utilized as an indicator of protozoan pathogens. Both oxidants highly depended on water pH and temperature in the spore inactivation. Since redox potential of Fe(VI) is almost the same as that of ozone, spore inactivation efficiency of Fe(VI) was expected to be similar with that of ozone. However, it was found that ozone was definitely superior over Fe(VI): at pH 7 and 20°C, ozone with the product of concentration×contact time (C¯T) of 10mgL(-1)min inactivate the spores more than 99.9% within 10min, while Fe(VI) with C¯T of 30mgL(-1) min could inactivate 90% spores. The large difference between ozone and Fe(VI) in spore inactivation was attributed mainly to Fe(III) produced from Fe(VI) decomposition at the spore coat layer which might coagulate spores and make it difficult for free Fe(VI) to attack live spores.